Loss Analysis of Optical Directional Couplers - Uenverdi, N. Aydan; Uenverdi, Necmiye Özlem (IEEE, 2007)
In this study, the power losses of TE and TM modes in optical directional couplers are analyzed. Identical, weakly guiding, lossless and slab optical waveguides are assumed to be weakly coupled to each other. The analysis shows that the losses due to inter-TE-modes coupling are higher than those due to inter-TM-modes coupling. The results also indicate that the coupling between pair TE modes is higher than the coupling between other modes and that the maximum coupling occurs between modes that have the same propagation constant.